Analisis Pengaruh Pertumbuhan Ekonomi, Investasi, Dan Indeks Pembangunan Manusia Terhadap Ketimpangan Antarkawasan Di Provinsi Jawa Tengah Tahun 2016-2021 - Mardani, Muhammad Rizky; Hayati (JURNAL ECONOMINA, 2024)
Inequality is a long-term macroeconomic problem faced by every country. This research discusses the inequality between regions in Central Java Province, focusing on various strategic areas. This inequality is measured using the Williamson Index which describes the difference in per capita income between regions. This study aims to analyze the influence of economic growth, investment, and human development index on inequality between regions in Central Java Province in 2016-2021. The approach taken in this study is quantitative with secondary data obtained from the Indonesian Central Statistics Agency (BPS) in 2016-2021. The method used to analyze the factors affecting inequality between regions in Central Java Province in 2016-2021 was the analysis of the Williams index and panel data regression. Based on the results of the study, it was shown that partially economic growth and the Human Development Index (HDI) had a positive and significant effect while investment had a negative but not significant effect on inequality between regions in Central Java Province. Simultaneously, economic growth, investment, and the Human Development Index (HDI) have a significant effect on inequality between regions in Central Java Province.